Designing of double-threaded intramedullary pin and evaluation of ex vivo biomechanical resistance to axial compression load on the canine long bone fracture gap model - Vora, Shruti; Kumar, Ashwani; Kaur, Kirandeep (The Indian Journal of Animal Sciences, 2022)
Intramedullary (IM) pinning is a biological method of fracture fixation; but is associated with complications ofpin migration, proximal fragment collapse and rotational instability. The study aimed to design double threaded(DT) IM pin and evaluated its biomechanical resistance to axial compression load in comparison to end-threaded(ET) and simple Steinman (SS) IM pin on the canine long bone fracture gap model. The DT IM pin was designedconsidering various morphometric measurements (17 femur and 8 tibia bones) on lateral radiographs of the routinely done healthy dogs. For ex vivo biomechanical study, a distal third fracture was created in the 17 (8 femoral, 9 tibial) canine cadaveric bones. A normograde IM pinning using SS, ET and DT was done keeping atleast 10 mm gap at the fracture site (fracture gap-model). A pin occupying 60-70% of the narrowest medullary canal was used for ETand DT, and >80% for SS models. The bone-implant constructs were subjected to axial compression load (N) till5 mm displacement of the proximal bone fragment or till dislodgement of the implant using 0.5 mm/min velocity ona servo-hydraulic testing machine. The magnitude of the axial compression load/mm displacement was influencedby the bone (femur vs tibia) and implant types. In femur, the DT pins sustained higher compression loads followedby SS and ET. However, for tibia, the load required was highest with DT followed by ET and SS pin. The studyreports the first of its kind indigenously designed biomechanically superior double threaded pin for the canine longbone fracture fixation